Screen-printed nickel–zinc batteries: a review of additive manufacturing and evaluation methods - Nazri, Muhamad Aiman; Lim, Lai Ming; Samsudin, Zambri; Tura Ali, Mohd Yusof; Mansor, Idris; Muhammad Irsyad Suhaimi, Muhammad Irsyad Suhaimi; Meskon, Shahrul Razi; Nordin, Anis Nurashikin (Mary Ann Liebert, Inc, 2021)
The advent of personalized wearable devices has boosted the demand for portable, compact power sources. Compared with lithographic techniques, printed devices have lower fabrication costs, while still maintaining high throughput and precision. These factors make thick film printing or additive manufacturing ideal for the fabrication of low-cost batteries suitable for personalized devices. This article provides comprehensive guidelines for thick-film battery fabrication and characterization, with the focus on printed nickel–zinc (Ni-Zn) batteries. Ni-Zn batteries are a more environmental-friendly option compared with lithium-ion batteries (LIBs) as they are fully recyclable. In this work, important battery fundamentals have been described, especially terms of electrochemistry, basic design approaches, and the printing technology. Different design approaches, such as lateral, concentric, and stacked, are also discussed. Printed batteries can be configured as series or parallel constructions, depending on the power requirements of the application. The fabrication flow of printed battery electrodes for the laboratory-scale prototyping process starts from chemical preparation, mixing, printing, drying, pressing, stacking to finally sealing and testing. Of particular importance is the process of electrolyte injection and pouch sealing for the printed batteries to reduce leakage. This entire process flow is also compared with industrial fabrication flow for LIBs. Criteria for material and equipment selection are also addressed in this article to ensure appropriate electrode consistency and good performance. Two main testing methods cyclic voltammetry for the electrodes and charge–discharge for the battery are also explained in detail to serve as systematic guide for users to validate the functionality of their electrodes. This review article concludes with commercial applications of printed electrodes in the field of health and personalized wearable devices. This work indicates that printed Ni-Zn and other zinc alkaline batteries have a promising future. The success of these devices also opens up different areas of research, such as ink rheology, composition, and formulation of ink using sustainable sources.